ARCHITECTURE AND ART: BAD RELATIONSHIPS - Herrera Ysla, Nelson (Archipielago. Revista cultural de nuestra América, 2010)
It has been a long time since relationships between architecture and art, traditionally complex, have been stressed more than our imagination can reach; a proof of this is the degradation of contemporary cities, in diverse latitudes. Nelson Herrera Ysla, Cuban architect, writer and art critic analyzes in this essay the reality of this phenomenon in his homeland, particularly in the City of Habana. He proposes to reevaluate the concept of environmental culture and, specifically, of architecture, as a key question at every moment in the historical flux of society.